IMPLEMENTASI BAHAN AJAR FIQIH IBADAH DALAM PENINGKATAN CAPAIAN HASIL BELAJAR MAHASISWA - firdaus, Firdaus MH (JURNAL ISLAMIKA, 2021)
Abstract Muamalah fiqh learning is needed to increase students' knowledge insight in the field of Sharia Economic Law, as a basic foundation for establishing laws governing human relations with others, especially in economic matters. The actualization of lecturers 'professionalism values ​​in the form of teaching of the Fiqh Muamalah textbook can be a problem solving problem in increasing students' understanding in the field of Islamic Economics Law to be more practical and effective. The research method with the Qualitative Descriptive approach is to build an increase in the achievement of muamalah fiqh learning outcomes by applying the use of muamalah fiqh textbooks the actualization design product in the student learning process. The results of this study indicate that 72% are able to achieve a value (> 85); 16% are able to reach indigo (81-85); 4% are able to reach indigo (76-80); 4% are able to reach indigo (66-70); and 4% are able to reach indigo (51-60). From these results it can be concluded that the application of Muqalah Fiqh textbooks the results of Actualization activities can improve the achievement of excellent learning outcomes for most student Keyword: Textbooks, Fiqh Muamalah, Access to Learning Outcomes